Bottle Cap Media for Developing Cognitive Skills in Early Childhood: Media Tutup Botol untuk Mengembangkan Keterampilan Kognitif pada Anak Usia Dini - Rahmawati, Siti; Azwir, Azwir; Maruddani, Raoda Tul Jannah; Mardiana, Mardiana; Dewi, Novriana (Universitas Muhammadiyah Sidoarjo, 2023)
General Background: Early childhood cognitive development requires concrete and engaging media to stimulate thinking and problem-solving skills. Specific Background: In many preschools, low-cost and recyclable materials have not been fully utilized to optimize children’s learning experiences. Knowledge Gap: Limited studies have specifically investigated the role of bottle cap media in supporting multiple aspects of cognitive development. Aim: This study explores how bottle cap media contributes to the improvement of cognitive abilities in children aged 5–6 years at TK Pertiwi IX Kota Jambi. Results: Using a qualitative descriptive approach with 15 children and 2 teachers, data were collected through observation, interviews, and documentation. Findings show that 80% of children demonstrated significant progress in recognizing colors (87%), grouping shapes (73%), counting objects (80%), and matching letters or numbers (67%). Novelty: The study highlights the innovative use of bottle caps as an accessible, sustainable, and enjoyable learning medium. Implications: The results suggest that recycled materials like bottle caps can effectively support early childhood education by enhancing cognitive skills while promoting creativity and environmental awareness. Highlights: Bottle caps foster color, shape, number, and symbol recognition. 80% of children showed overall cognitive improvement. Recycled media provides sustainable and engaging learning tools. Keywords: Early Childhood, Cognitive Skills, Bottle Cap Media, Learning Activity, Recycled Materials